2014
DOI: 10.3168/jds.2014-8203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pathogen-specific clinical mastitis on probability of conception in Holstein dairy cows

Abstract: The objective of this study was to estimate the effects of pathogen-specific clinical mastitis (CM), occurring in different weekly intervals before or after artificial insemination (AI), on the probability of conception in Holstein cows. Clinical mastitis occurring in weekly intervals from 6 wk before until 6 wk after AI was modeled. The first 4 AI in a cow's lactation were included. The following categories of pathogens were studied: Streptococcus spp. (comprising Streptococcus dysgalactiae, Streptococcus ube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
1
28
1
1
Order By: Relevance
“…A first-order autoregressive correlation structure among the repeated measurements of milk yield and composition within a cow's lactation was incorporated. These models were adopted from earlier research on the effects of pathogen-unidentified or -specific CM on milk yield (Gröhn et al 2004;Wilson et al 2004;Bar et al 2007;Hertl et al 2014). Wilson et al (2004) showed a first-order autoregressive correlation structure among the repeated measurements of milk yield was the best structure in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A first-order autoregressive correlation structure among the repeated measurements of milk yield and composition within a cow's lactation was incorporated. These models were adopted from earlier research on the effects of pathogen-unidentified or -specific CM on milk yield (Gröhn et al 2004;Wilson et al 2004;Bar et al 2007;Hertl et al 2014). Wilson et al (2004) showed a first-order autoregressive correlation structure among the repeated measurements of milk yield was the best structure in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Direct and indirect economic losses due to mastitis have been estimated (Halasa et al., ) and vary greatly between animals and pathogens. For example, yield losses in heifers are greatest after E. coli CM and in multiparous animals after Klebsiella CM, and both coliforms have greater impact on fertility than other pathogen species (Hertl et al., , ). Yield losses may persist for months after coliform or GPCN mastitis, whilst CM with non‐aureus staphylococci does not cause reduced production (Hertl et al., ).…”
Section: Socio‐economic Impact and Zoonotic Aspectsmentioning
confidence: 99%
“…For example, yield losses in heifers are greatest after E. coli CM and in multiparous animals after Klebsiella CM, and both coliforms have greater impact on fertility than other pathogen F I G U R E 4 Faecal contamination is a major source of exposure to environmental pathogens regardless of the use of sawdust (left), straw (right) or other bedding material. Photographs: RN Zadoks species (Hertl et al, 2014a(Hertl et al, , 2014b. Yield losses may persist for months after coliform or GPCN mastitis, whilst CM with non-aureus staphylococci does not cause reduced production (Hertl et al, 2014a).…”
Section: Zoonotic Aspectsmentioning
confidence: 99%
“…Thus, in-depth understanding of disease mechanisms is critical to promote animal health and at the same time encourage judicious use of antibiotics in livestock. Mastitis is one of the most common diseases in dairy herds, and approximately 20% to 30% of dairy cows develop clinical mastitis at least once during lactation12. Not surprisingly, prophylaxis and treatment of mastitic cows are the major reasons for antibiotic usage in dairy farms34.…”
mentioning
confidence: 99%